Utilization Of Sugarbean Waste Through Bio Seeding Block As A Seeding Media Plants At Dusk Farm Banyuwangi: Pemanfaatan Limbah Ampas Tebu Melalui Bio Seeding Block Sebagai Media Pembibitan Tanaman Di Senja Farm Banyuwangi - Riza Rahimi Bachtiar; Ayu Purwaningtyas; Mohamad Ilham Hilal (Universitas Lancang Kuning, 2023)
Banyuwangi is one of the agricultural centers in East Java Province and nationally. Especially for vegetable horticultural commodities, several products have been able to become regional superiors and are able to penetrate the national market such as chili, eggplant, and mustard greens. In addition, the productivity of vegetable horticulture has increased from year to year. One of the MSMEs engaged in horticulture is Senja Farm. Senja Farm has a specific activity in producing hydroponic vegetables. These vegetables are cultivated and are able to produce healthier vegetables because they are minimal in pesticide residues. Hydroponic vegetables are vegetables that are grown with the help of liquids containing minerals needed by vegetables to grow through a process that is highly guarded by the method and place of planting and does not require soil. The use of pesticides in hydroponic planting techniques is also not necessary to protect against insect pests. This has an impact on the yield of hydroponic plants in the form of organic food. Consumption of organic vegetables in Banyuwangi has a trend that tends to increase so it is very potential to be developed. However, the hydroponic process at Senja Farm still relies on plant media derived from livestock compost and seedling media using plastic (polybag). The purpose of this PKM is to utilize bagasse waste through the use of bio-seeding blocks as planting media and as a substitute for seedling media. The output targets of this PKM activity are in the form of products submitted to partners, publications in national journals with ISSN, publications in print media and in the form of videos of the implementation of activities.